Sports : A Can-You-Find-It Book - Kukla, Lauren (Can you find it?, 2023)
"Score big with this fun seek-and-find title! Hundreds of objects are hidden inside full-color photo puzzles featuring your favorite sports. Each to-find list includes pictographs and word labels to engage pre-readers and early readers alike."